Principles of cost accounting - VanDerbeck, Edward J.; Nagy, Charles F. (Cincinnati, OH : South-Western College, 1999)
This book is about : Cost accounting; Accounting for materials, for labor, for factory overhead; Cost accounting for service businesses...
Keywords: Accounting; Economics; Cost accounting